PENGARUH KETAHANMALANGAN (AQ) TERHADAP MINAT BERWIRAUSAHA SISWA MENENGAH KEJURUAN - Nabila, Nabila; Supendi, Moh. (STKIP Persada Khatulistiwa Sintang, 2023)
Income statistics decline as the number of unemployed people rises. The interperial interest enterpreneurship to be developed as a solution to reduce unemployment. Therefore research is needed to examine the factors that can increase the interest in entrepreneurship among the younger generation. The purpose of this study was to determine the effect of Adversity quotient on vocational high school students' entrepreneurial interest. The population in this study were 130 students in grade XI at SMKN 22 Jakarta for the academic year 2022/2023, then from this population the sample was taken using a simple random sampling technique. The number of samples determined based on the slovin formula with a precision level of 5% is 98 samples which are rounded up to 100 samples which are used as respondents. Data collection uses a questionnaire, with data analysis techniques using simple linear regression. The results of this study indicate that adversity has a positive effect on students' interest in entrepreneurship at SMKN 22 Jakarta. Based on the results of this study, this means that if resilience is strengthened by students at SMKN 22 Jakarta, there is a possibility that students' interest in entrepreneurship at SMKN 22 Jakarta will increase